2012
DOI: 10.1093/cercor/bhr360
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MRI Analysis of the Corpus Callosum Reveals White Matter Differences in Presymptomatic and Early Huntington's Disease

Abstract: Recent magnetic resonance imaging (MRI) studies suggest that abnormalities in Huntington's disease (HD) extend to white matter (WM) tracts in early HD and even in presymptomatic stages. Thus, changes of the corpus callosum (CC) may reflect various aspects of HD pathogenesis. We recruited 17 HD patients, 17 pre-HD subjects, and 34 healthy age-matched controls. Three-dimensional anatomical MRI and diffusion tensor images of the brain were acquired on a 3T scanner. Combining region-of-interest analyses, voxel-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
58
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 54 publications
12
58
0
2
Order By: Relevance
“…In agreement with previous studies [Di Paola et al, 2012;Rosas et al, 2010], we found that the isthmus was the CC sub-region most affected in PreHD subjects. Our DTI analysis detected FA and RD differences only in the isthmus of PreHD subjects.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies [Di Paola et al, 2012;Rosas et al, 2010], we found that the isthmus was the CC sub-region most affected in PreHD subjects. Our DTI analysis detected FA and RD differences only in the isthmus of PreHD subjects.…”
Section: Discussionsupporting
confidence: 93%
“…As in our previous study [Di Paola et al, 2012], scans were collected in a single session with the following pulse sequences: (a) proton density (PD) and T2-weighted double turbo spin-echo (SE) sequences acquired in transverse planes (TR: 4500 ms, TE: 12 ms, TE: 112 ms, FOV 2303172 mm, matrix 3203240, slice thickness: 5 mm, number of slices: 24); (b) fluid-attenuated inversion-recovery (FLAIR) sequences in the same planes as the SE sequences (TR/ TE/TI: 8500/109/2000 ms; FOV: 2303168 mm, matrix: 2563256, slice thickness: 5 mm, number of slices: 24); (c) T1-weighted 3D images, with partitions acquired in the sagittal plane, using a modified driven equilibrium Fourier transform (MDEFT) [Deichmann et al, 2004] sequence isotropic voxels); (d) diffusion-weighted volumes were also acquired using spin-echo echo-planar imaging (TE/ TR: 89/8500 ms, bandwidth: 2126 Hz/vx; matrix: 128x128; 80 axial slices, voxel size: 1.8x1.8x1.8 mm) with 30 isotropically distributed orientations for the diffusion sensitizing gradients at a b-value of 1,000 s/mm 2 and 6 b 5 0 images. Scanning was repeated three times and averaged to increase the signal-to-noise ratio; (e) and six consecutive T2*-weighted gradient echo-planar imaging sequences at different echo times (TE) (TEs: 6,12,20,30,45 and 60 ms; TR 55,000; bandwidth 5 1116 Hz/vx; matrix size 128 x 128 x 80; flip angle 90 ; voxel size of 1.5 x 1.5 x 2 mm 3 ) Peran et al, 2009].…”
Section: Mri Data Acquisitionsupporting
confidence: 59%
See 1 more Smart Citation
“…Additionally, its functional differentiation along an elongated sagittal axis has allowed researchers to focus on 2D analyses of the mid-sagittal section. The structural MRI based CC structure has been used to study a variety of human development and diseases including Autism (Vidal et al 2006; Tepest et al 2010), Schizophrenia (Joshi et al 2013; Adamson et al 2011), Huntington’s disease (Di Paola et al 2012) and others. Starting from our prior work on volumetric Laplace-Beltrami operator and mTBM (Wang et al 2004a; Wang et al 2010), here we show that we may integrate two different sets of shape features efficiently for 3D CC structural analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Intuitively, thickness and mTBM are complementary, as thickness describes distances roughly along the surface’s normal direction, while mTBM detects surface dissimilarities, including differences in the surface metric tensor induced by the particular surface parameterization. So we hypothesize that the combination of thickness and mTBM will offer a complete set of surface statistics for callosal morphometry and that it may boost statistical power to detect the impacts of visual experience in the CC compared to 2D mid-sagittal analyses (Thompson et al 2003; Luders et al 2006; Luders et al 2010; Tepest et al 2010; Adamson et al 2011; Di Paola et al 2012; Herron et al 2012). …”
Section: Introductionmentioning
confidence: 99%